Sobre as publicações de cuidados paliativos em periódicos brasileiros de terapia ocupacional: uma revisão da literatura - MACEDO, Julliana Karolina da Silva (2023)
This research aimed to perform a literature review of the texts published on Palliative Care in Brazilian Occupational Therapy journals to synthesize and explain what has been published in these journals. This study has as its characteristic the literature review and the Brazilian Occupational Therapy journals were: USP's Occupational Therapy Journal, UFSCar's Brazilian Occupational Therapy Notebooks, CETO (Occupational Therapy Specialties Center), Revista Baiana de Occupational Therapy and the REVISBRATO (Brazilian Interinstitutional Journal of Occupational Therapy), we considered the editions from the first volume of each journal until the year 2018. We found 11 articles that met the inclusion criteria. It was observed that the year 2015 was the most published, the region that stood out most in publications, was the Southeast region of Brazil, as well as that the hospital was the context presented as places to conduct these research published in these periodicals. Thus, based on the criteria applied in this study, the research published in the Brazilian Occupational Therapy journals on palliative care is recent and still very few, when compared with the number of journals publications, therefore, it is encouraged that further research be conducted. and published in these journals to deepen these studies in palliative care.